2017
DOI: 10.1111/jmwh.12638
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Spontaneous Births Attended by Midwives and Physicians in US Hospitals in 2014

Abstract: In 2014, midwives practicing in US hospitals attended women with a range of risks similar to those of women attended by physicians. Small but statistically significant differences were noted in most characteristics and should be controlled in comparative studies. This contrasts with earlier reports of midwives caring for disproportionately disadvantaged women compared to physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A review of 2014 birth certificate data for spontaneous vaginal births in hospitals showed that women with births attended by midwives vs. physicians were demographically similar on key variables such as age, race, education, marital status, and insurance type. 18 Though women who birth in community settings (e.g., home or freestanding birth center) are disproportionately white according to 2018 vital statistics data, 15 a study of a national sample of birth centers using 2007-2010 data reports 23% of birth center births were to nonwhite women. 6 That same study found that only 24% of birth center births were to Medicaid participants, far below the proportion of births covered by Medicaid.…”
mentioning
confidence: 99%
“…A review of 2014 birth certificate data for spontaneous vaginal births in hospitals showed that women with births attended by midwives vs. physicians were demographically similar on key variables such as age, race, education, marital status, and insurance type. 18 Though women who birth in community settings (e.g., home or freestanding birth center) are disproportionately white according to 2018 vital statistics data, 15 a study of a national sample of birth centers using 2007-2010 data reports 23% of birth center births were to nonwhite women. 6 That same study found that only 24% of birth center births were to Medicaid participants, far below the proportion of births covered by Medicaid.…”
mentioning
confidence: 99%
“…The argument has been made that studies comparing birth outcomes between provider types without stratifying for women’s risk status result in apples to oranges comparisons. Thornton (2017) examined the characteristics of spontaneous vaginal births attended by CNMs and physicians in U.S. hospitals and reported that in U.S. hospitals CNMs cared for women with a range of risks similar to those of women who were attended by physicians. Women who were cared for by CNMs had fewer labor inductions, epidural analgesia use, third- and fourth-degree lacerations, and newborn admissions to the neonatal intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review identified exclusively U.S.-based studies and found similar results, with equivalent or superior outcomes in initiating breastfeeding, operative and cesarean births, and perineal lacerations (Newhouse et al, 2011 ). Additional research since 2011 confirmed Newhouse et al's finding (Hamlin, 2017 ;Thornton, 2017 ). From a policy perspective, midwifery care can be a cost-effective and sustainable approach to meeting society's women's healthcare needs (Renfrew et al, 2014).…”
Section: Nurse-midwivesmentioning
confidence: 91%
“…Births attended by CNMs and CMs occur primarily in hospitals; more than 94% of births in the United States occurred in hospitals in 2014, although the number of home and freestanding birth center births has been rising (ACNM, 2018 ;MacDorman, Mathews, & Declercq, 2014 ). Research has demonstrated fewer interventions, including lower cesarean birth rates, among CNM-attended births versus physician-attended births, as well as outcomes at least comparable to physician-attended births (Blanchette, 1995 ;Hamlin, 2017 ;MacDorman & Singh, 1998 ;Newhouse et al, 2011 ;Rosenblatt et al, 1997 ;Thornton, 2017 ).…”
Section: Nurse-midwivesmentioning
confidence: 99%